2000
DOI: 10.1002/(sici)1521-401x(200001)28:1<15::aid-aheh15>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Products and Kinetics of the OH-radical-induced Dealkylation of Atrazine

Abstract: Hydroxyl radicals, generated radiolytically in N2O/O2‐saturated solutions, yield in their reaction with atrazine equal amounts of deethylatrazine and acetaldehyde (40% of OH radical yield) and deisopropylatrazine and acetone (16%), respectively. The precursors of deethylatrazine and acetaldehyde is their Schiff base which hydrolyzes slowly (OH–‐catalyzed: k = 5.2 dm3 mol–1 s–1). The hydrolysis of the Schiff base of deisopropylatrazine and acetone is too fast to be detected. In a pulse radiolysis experiment, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
72
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 40 publications
(56 reference statements)
6
72
0
2
Order By: Relevance
“…On the other hand, though very slow, • OH reacts with OOOT as at least 30% OOOT is degraded after about a radiation dose of 8000 Gy. It can be reasonably assumed that • OH undergoes addition reaction with OOOT based on the earlier understanding that • OH reacts with many of the triazine ring by addition [11,15,17].…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…On the other hand, though very slow, • OH reacts with OOOT as at least 30% OOOT is degraded after about a radiation dose of 8000 Gy. It can be reasonably assumed that • OH undergoes addition reaction with OOOT based on the earlier understanding that • OH reacts with many of the triazine ring by addition [11,15,17].…”
Section: Resultsmentioning
confidence: 72%
“…The pattern of reaction of • OH with a number of triazine derivatives is reasonably well documented [11,15,16]. • OH undergoes either addition or hydrogen abstraction reaction with atrazine [15,16]. It was also shown that the major end product of oxidation of atrazine by • OH is cyanuric acid (OOOT) [17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the rate constants for solvated electrons (e aq − ) with carbonate, bicarbonate and nitrate ions were determined as 3.5 × 10 5 M −1 s −1 , 1.0 × 10 6 M −1 s −1 and 9.7 × 10 9 M −1 s −1 , respectively [22][23][24], consequently a decrease of solvated electrons was expected. In addition, the rate constant for reaction of OH • with atrazine was determined as 3.0 × 10 9 M −1 s −1 [26], whereas the rate constant for reaction of solvated electrons (e aq − ) with atrazine was determined as 4.8 × 10 9 M −1 s −1 [17]. Moreover the radiolytic behavior of atrazine in water is not totally clear whether it follows oxidation reactions [13] or reduction reactions [17,20] and consequently radiolytic degradation of atrazine decreases with increase of groundwater scavengers concentrations due to competition reactions of atrazine and scavengers for OH • radicals and solvated electrons (e aq − ).…”
Section: Resultsmentioning
confidence: 95%